2013
DOI: 10.1128/genomea.00084-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Vibrio mimicus Strain CAIM 602 T

Abstract: Vibrio mimicus is a Gram-negative bacterium associated with gastrointestinal diseases in humans around the world. We report the complete genome sequence of the Vibrio mimicus strain CAIM 602T (CDC1721-77, LMG 7896T, ATCC 33653T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
0
4
0
7
Order By: Relevance
“…mimicus strains were sequenced using a semiconductor NGS platform (Ion Torrent Personal Genome Machine sequencer, Life Technologies) with a 316 chip at CIAD Mazatlán. The reads were assembled with the program Newbler ver.2.3 mapping against CAIM 602 T [ 31 ]. A genome-wide assembly and contig synteny was constructed with Mauve Genome Alignment software ver.…”
Section: Methodsmentioning
confidence: 99%
“…mimicus strains were sequenced using a semiconductor NGS platform (Ion Torrent Personal Genome Machine sequencer, Life Technologies) with a 316 chip at CIAD Mazatlán. The reads were assembled with the program Newbler ver.2.3 mapping against CAIM 602 T [ 31 ]. A genome-wide assembly and contig synteny was constructed with Mauve Genome Alignment software ver.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Vibrio mimicus , the closely related Vibrio species of V. cholerae , can also share important virulence factors such as enterotoxins or haemolysins, suggesting contemporary horizontal transfer of the CTX and VPI prophages (Boyd, Moyer, Shi, & Waldor, ). It can be isolated from a large number of environmental sources such as fresh, brackish and sea water (Campos et al., ; Guardiola‐Avila et al., ). V. mimicus has been linked to foodborne illnesses in recent years causing sporadic cases of diarrhoea with cholera‐like signs (Guardiola‐Avila et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nine genomes of V. mimicus were analyzed in this study. The genomes of V. mimicus CAIM-602 T (Vm602, PRJNA179483) [ 7 ], V. mimicus CAIM-1882 (Vm1882, PRJNA219179), V. mimicus CAIM-1883 (Vm1883, PRJNA219181) [ 20 ], and V. mimicus ATCC-33654 (Vm 33654, PRJNA231624) were sequenced by our research group, as previously reported [ 7 , 20 ]. The remaining five genomes sequences were obtained from the database of the National Center for Biotechnology Information (NCBI): V. mimicus MB451 (Vm451, PRJNA40509), V. mimicus VM223 (Vm223, PRJNA40483), V. mimicus VM603 (Vm603, PRJNA40241), V. mimicus VM573 (Vm573, PRJNA40243), and V. mimicus SX-4 (Vm SX4, PRJNA47421) [ 6 , 10 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Vibrio mimicus has been recognized as an emergent pathogen in human diseases, and it has been isolated from cases of gastroenteritis, ear infections, and severe cholera-like diarrhoea, as well as from several marine products, aquatic plants, sediments, and water (marine, brackish, and freshwater) [ 3 , 4 , 5 ]. V. mimicus strains encode a wide variety of virulence factors, such as he, hemagglutinins, pili, metalloproteases, enterotoxins, and siderophores, which are mediated by several different mechanisms [ 5 , 6 , 7 , 8 ]. Moreover, studies of comparative genomics of Vibrio species have shown that genetic exchange among Vibrionaceae family species is a continuous process [ 6 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%